Turmeric: from spice to cure. A review of the anti-cancer, radioprotective and anti-inflammatory effects of turmeric sourced compounds - Cozmin, Mihai; Lungu, Ionut Iulian; Gutu, Cristian; Stefanache, Alina; Duceac, Letitia Doina; Șoltuzu, Bogdan Dorin; Damir, Daniela; Calin, Gabriela; Bogdan Goroftei, Elena Roxana; Grierosu, Carmen; Boev, Monica (Frontiers in Nutrition, 2024)
Turmeric (Curcuma longa) has been extensively studied for its diverse pharmacological properties, including its potential role as an anticancer agent, antioxidant, and radioprotector. This review provides an overview of the chemical composition of turmeric, focusing on its main bioactive compounds, such as curcuminoids and volatile oils. Curcumin, the most abundant curcuminoid in turmeric, has been widely investigated for its various biological activities, including anti-inflammatory, antioxidant, and anticancer effects. Numerous in vitro and in vivo studies have demonstrated the ability of curcumin to modulate multiple signaling pathways involved in carcinogenesis, leading to inhibition of cancer cell proliferation, induction of apoptosis, and suppression of metastasis. Furthermore, curcumin has shown promising potential as a radioprotective agent by mitigating radiation-induced oxidative stress and DNA damage. Additionally, turmeric extracts containing curcuminoids have been reported to exhibit potent antioxidant activity, scavenging free radicals and protecting cells from oxidative damage. The multifaceted pharmacological properties of turmeric make it a promising candidate for the development of novel therapeutic strategies for cancer prevention and treatment, as well as for the management of oxidative stress-related disorders. However, further research is warranted to elucidate the underlying mechanisms of action and to evaluate the clinical efficacy and safety of turmeric and its bioactive constituents in cancer therapy and radioprotection. This review consolidates the most recent relevant data on turmeric's chemical composition and its therapeutic applications, providing a comprehensive overview of its potential in cancer prevention and treatment, as well as in radioprotection.